Honor Killing di Diaspora Barat: Konstruksi dan Respons Hukum Pidana di Inggris, Jerman, dan Kanada - Zul Khaidir Kadir (PT. Hasba Edukasi Mandiri, 2026)
Honor killing in Western diasporas remains a serious concern because migration to host states does not automatically dismantle the logic of honor that ties family reputation to the control of women’s bodies, intimate relations, and life choices. This study examines the relationship between honor, migration, community identity, and patriarchy; identifies the patterns, triggers, and forms of honor-based violence; and analyzes legal responses and prevention strategies in the United Kingdom, Germany, and Canada. The research employs normative legal methodology through statutory, case-based, and comparative approaches. Primary legal materials consist of legislation and judicial decisions, supported by secondary materials on honor, diaspora, gender-based violence, and victim protection. The analysis finds that honor in diaspora settings no longer functions merely as a private family concern, but also as a means of preserving minority community boundaries under pressures of assimilation and intergenerational tension. Violence then develops through an escalating continuum, beginning with surveillance, restrictions on mobility, threats, forced marriage, and social isolation, and in some cases ending in homicide. The United Kingdom and Canada illustrate stronger preventive mechanisms through forced marriage protection and criminal law measures, while Germany demonstrates a firm rejection of honor-based motives through general homicide law. The study argues that effective responses require a combination of legal firmness, accessible early protection, and institutional sensitivity that does not slide into either cultural permissiveness or the stigmatization of minority communities.